Drug monitoring in child and adolescent psychiatry for improved efficacy and safety of psychopharmacotherapy - Fegert Jörg M; Antony Gisela; Kirchheiner Julia; Kölch Michael; Mehler-Wex Claudia; Gerlach Manfred (BMC, 2009)
Abstract Most psychotropic drugs used in the treatment of children and adolescents are applied "off label" with a direct risk of under- or overdosing and a delayed risk of long-term side effects. The selection of doses in paediatric psychiatric patients requires a consideration of pharmacokinetic parameters and the development of central nervous system, and warrants specific studies in children and adolescents. Because these are lacking for most of the psychotropic drugs applied in the Child and Adolescent and Psychiatry, therapeutic drug monitoring (TDM) is a valid tool to optimise pharmacotherapy and to enable to adjust the dosage of drugs according to the characteristics of the individual patient. Multi-centre TDM studies enable the identification of age- and development-dependent therapeutic ranges of blood concentrations and facilitate a highly qualified standardized documentation in the child and adolescent health care system. In addition, they will provide data for future research on psychopharmacological treatment in children and adolescents, as a baseline for example for clinically relevant interactions with various co-medications. Therefore, a German-Austrian-Swiss "Competence Network on Therapeutic Drug Monitoring in Child and Adolescent Psychiatry" was founded <abbrgrp>1</abbrgrp> introducing a comprehensive internet data base for the collection of demographic, safety and efficacy data as well as blood concentrations of psychotropic drugs in children and adolescents.